Needs Assessment for Developing a Computational Thinking-Based Computer Application Textbook - Hasriadi, Misykat Malik Ibrahim, Yuspiani, Syamsuddin, Syahruddin Usman, M. Yusuf T, Ilyas Ismail (Journal of Educational Studies, 2025)
This study aims to identify the needs for developing a computational thinking-based computer application textbook at the Faculty of Tarbiyah and Teacher Training, UIN Palopo, Indonesia. This research constitutes the analysis phase of a Research and Development study employing the ADDIE model. Data were collected through questionnaires (N=98 pre-service teachers), semi-structured interviews with two lecturers, curriculum document analysis (CPL, CPMK, RPS), and resource observation. Descriptive statistics and Miles-Huberman thematic analysis were used to analyze the data. The findings reveal three multidimensional gaps: (1) Applicative gap: 73.5% of students mastered basic functions, but 56.1% struggled to apply them for creating learning media; (2) Cognitive gap: 83.7% required systematic thinking guidance (computational thinking) that has not been explicitly integrated into learning objectives; (3) Contextual gap: 87.8% demanded materials relevant to teaching profession tasks. Learner profile analysis showed high motivation (mean 4.19/5) but varied practical experience (mean 3.34/5). Resource analysis confirmed the availability of laboratories and competent lecturers, yet with quantitative limitations in technology infrastructure. The conclusion confirms that multidimensional gaps necessitate the development of an integrated, contextual, and problem-solving-oriented computational thinking-based textbook. This needs analysis provides a foundational rationale for instructional design decisions in subsequent development phases.